The Relationship Between Mothers’ Umbilical Cord Care and The Time of Umbilical Cord Detachment among Infants at Pidie Health Center, Pidie District - Juliati Juliati; Kasmawati Kasmawati; Cut Nana Mutia (Universitas Serambi Mekkah, 2022)
Umbilical cord is a connective tissue that connects the placenta and fetus. It is the lifeline for a fetus in the womb because it supplies nutrients and oxygen to the fetus for 9 months and 10 days. The rest of the umbilical cord attached to the baby's stomach (umbilical stump) will usually dry up and fall off on its own within 1-3 weeks although some may come off after 4 weeks. The purpose of this study was to determine the relationship between the ways umbilical cord is cared and the time of umbilical cord detachment among infants at the Pidie Public Health Center, Pidie District. The research samples were women with babies in the working area of the Pidie Public Health Center, totaling 32 people. This study is descriptive in nature. It used a cross sectional design to find out the relationship between umbilical cord care and the time of umbilical cord detachment in infants. The findings revealed that 53.1% (17 respondents) found the umbilical cord detachment in infants was fast, and 62.5% (20 respondents) found the umbilical cord care in infants was relatively fast. The data on the relationship between umbilical cord separation and umbilical cord care in infants were obtained from 20 respondents with good umbilical cord care. It is expected that all mothers in the working area of the Pidie Public Health Center can gain updated information on umbilical cord care because it can accelerate the removal of the umbilical cord on infants. Keywords: Knowledge, Umbilical Cord Care, Umbilical Cord Removal Time